Clouds and their effects on solar radiation in São Paulo - Santana, Jorge Rosas (2018)
Clouds and their instantaneous effects on downward solar radiation were studied at the Metropolitan Area of São Paulo. For this purpose, visual observations of clouds, ground-based measurements performed by different radiometers, products from the polar orbiting satellites CALIPSO and CloudSat and 1-D Radiative Transfer Model (RTM) LibRadtran were used. Daytime climatology of cloud cover fraction (1958-2016) using data of hourly visual observations was carried out. The diurnal cycle of cloud cover fraction was dominated by low clouds especially by stratiform clouds. Remarkable differences in the diurnal cycles of low cumuliform and stratiform clouds were also observed. During the time period, positive trends for low cloud cover (1.6 %/decade), especially stratiform (3.1 %/decade), and cirriform cloud (0.8 %/decade) were observed, while a decreasing trend of mid-level cloud cover (-2.4%/decade) was found. Seasonal and diurnal variability of vertical profile of cloud was observed, with cloud extending to higher altitudes at night and with maximum frequency of occurrence observed in summer. In winter, low clouds prevailed. Effective cloud optical depth (ECOD), using the total transmittance at 415 nm, and instantaneous cloud effects on solar radiation at the surface, using global irradiance measurements, were estimated in synergy with LibRadtran computations. ECOD presented seasonal and diurnal variability, with maximum of mean in spring (34.4) and in the afternoon (34.2), and minimum at sunrise (25.5) and winter (26.9) for low clouds. The shortwave effects of clouds depended on solar disk condition, cloud type and cloud cover. Maximum of shortwave radiative attenuation was observed for low clouds in total overcast conditions with a median reduction of 72 % of global irradiance compared to clear sky. Median reduction of mid and high clouds was 57 % and 33 %, respectively. Enhancement effects with duration as long as 20 minutes, caused by lateral scattering, were observed in the presence of all analyzed cloud types, when the solar disk was not blocked by clouds, increasing global solar irradiance around 10% at the surface. Maximum enhancement could reach 50 % for low clouds.